2020
DOI: 10.1038/s41598-020-60065-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional omics analyses reveal only minor effects of microRNAs on human somatic stem cell differentiation

Abstract: The contribution of microRNA-mediated posttranscriptional regulation on the final proteome in differentiating cells remains elusive. Here, we evaluated the impact of microRNAs (miRNAs) on the proteome of human umbilical cord blood-derived unrestricted somatic stem cells (USSC) during retinoic acid (RA) differentiation by a systemic approach using next generation sequencing analysing mRNA and miRNA expression and quantitative mass spectrometry-based proteome analyses. Interestingly, regulation of mRNAs and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Complementary data displayed in Supplementary Figure 3. (C) Gene set enrichment analysis (GSEA) of 57 direct RFX7 target genes in human p53-negative HL-60 promyelocytes differentiated into macrophages or neutrophils (upper panels) (47), human umbilical cord blood-derived unrestricted somatic stem cells (USSC) differentiated into neuronal-like cells (48) and human pluripotent stem cells (PSC) differentiated into lung alveolar cells (bottom panels) (49).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Complementary data displayed in Supplementary Figure 3. (C) Gene set enrichment analysis (GSEA) of 57 direct RFX7 target genes in human p53-negative HL-60 promyelocytes differentiated into macrophages or neutrophils (upper panels) (47), human umbilical cord blood-derived unrestricted somatic stem cells (USSC) differentiated into neuronal-like cells (48) and human pluripotent stem cells (PSC) differentiated into lung alveolar cells (bottom panels) (49).…”
Section: Resultsmentioning
confidence: 99%
“…Publicly available RNA-seq data from human p53-negative HL-60 promyelocytes differentiating into macrophages or neutrophils was obtained from GEO accession number GSE79044 (47). Publicly available RNA-seq data from of human umbilical cord blood-derived unrestricted somatic stem cells (USSC) differentiating into neuronal-like cells was obtained from GEO accession number GSE96642 (48). Publicly available RNA-seq data from human pluripotent stem cells differentiating into lung alveolar cells was obtained from GEO accession number GSE96642 (49).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MicroRNAs (miRNAs) are highly conserved small RNAs, 20-22 nucleotides in length, which modulate protein function via directly binding to the 3'-untranslated region (3'-UTR) of their target mRNAs ( 11 ). Recent studies have demonstrated that changes in miRNA levels are involved in numerous diseases, including myocardial ischemia ( 12 ), inflammation ( 13 ), diabetes ( 14 ) and CH ( 4 , 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%